A preliminary review of the cultural heritage and emerging pilgrimage tourism in Tamil Nadu / V. Sivakumar ... [et al.] - Sivakumar, V.; Saranya, P. R.; Iyappan, A.; Leelapriyadharsini, S. (Faculty of Hotel & Tourism Management, 2019)
Pilgrimage Tourism has become an emergent form of domestic tourism with the expanding demand for religious travel along with the accomplishment of other religious obligations. It can also be considered as a catalyst for socio-economic development of the neighbourhood community involved directly and indirectly for the pilgrims during their sojourns at the sacred sites. Though Pilgrimage Tourism is considered as the bottom of the tourism business pyramid, much value can be added through numerous attractive and affordable packages. This paper deals with the concern and challenges of pilgrimage tourism and the impact of cultural heritage in southern districts of Tamil Nadu. Prospects of religious tourists and the impact of cultural heritage are also explored in this research paper.